2022
DOI: 10.1002/jsfa.12081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of over crop and reduced yield by cluster thinning on phenolic and volatile compounds of grapes and wines of ‘Sangiovese’ trained to Tendone

Abstract: BACKGROUND ‘Sangiovese’ (Vitis vinifera L.) is a well‐known Italian wine grape utilized for producing the prestigious Chianti Classico brand. Here, ‘Sangiovese’ is generally trained to a vertical training system, with an imposed crop level of around 3–5 kg per vine to preserve grape quality. Tendone comprises a horizontal trellis system, largely diffused in Mediterranean Countries for table grape production, and is adopted to achieve a high yield and to preserve grapes, by means of its canopy architecture, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Starting from anthocyanins, seven compounds were unequivocally identified—delphinidin-3 O -glucoside, cyanidin-3 O -glucoside, petunidin-3 O -glucoside, peonidin-3 O -glucoside, and malvidin-3 O -glucoside—because of the matching with commercial standards, while peonidin-3 O - trans -coumaroylglucoside (POCG) and malvidin-3 O - trans -coumaroylglucoside (MCG) were identified due to their characteristic chromatographic and spectrophotometric behavior many times reported in the literature [ 14 , 15 ]. Conversely, insufficient information was available to correctly identify the other anthocyanin conjugates in the extracts ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from anthocyanins, seven compounds were unequivocally identified—delphinidin-3 O -glucoside, cyanidin-3 O -glucoside, petunidin-3 O -glucoside, peonidin-3 O -glucoside, and malvidin-3 O -glucoside—because of the matching with commercial standards, while peonidin-3 O - trans -coumaroylglucoside (POCG) and malvidin-3 O - trans -coumaroylglucoside (MCG) were identified due to their characteristic chromatographic and spectrophotometric behavior many times reported in the literature [ 14 , 15 ]. Conversely, insufficient information was available to correctly identify the other anthocyanin conjugates in the extracts ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…The tentative identification of the compounds in the extracts was achieved by matching the positions of absorption maxima (λ max ), absorption spectra profiles, and retention times (RT) with those from commercially available pure standards and studies already reported in the literature for comparable matrices [ 14 , 15 ]. Moreover, the quantification was performed using the calibration curves in the concentration range of 100–0.2 µg mL −1 of malvidin-3 O -glucoside (R 2 = 0.9983), caffeic acid (R 2 = 0.9988), epicatechin (R 2 = 0.9944), and gallic acid (R 2 = 0.9991).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to previous descriptions [29], the "tendone" allows controlling cluster temperature (grape berries were on average 2 • C below ambient), because it improves the canopy management protecting the grapes from direct UV radiation and avoids the sun-burning of berries. Moreover, during the ripening stage, the grapes experience diffuse light that avoids the different coloring between the shaded and the exposed parts of the bunches.…”
Section: Plant Materials and Growth Conditionmentioning
confidence: 92%
“…Similar to our study, De Bei et al [29] found that shoot thinning does not improve berry composition when no considerable differences in yield are obtained with this practice. However, if a considerable difference in crop size among treatments is obtained by shoot thinning or cluster thinning, in most cases, the concurrent reduction of both sugar and anthocyanins is obtained with increased yield [51][52][53][54]. In the context of climate change and the associated problems with high sugar concentration in grape berries in warm seasons [2], the practice of increasing yield may be appropriate to reduce the accumulation of sugar in berries, although it may not be convenient if a high intensity of grape and wine color is desired [55].…”
Section: Study Of Severe Shoot Trimming Combined With Crop Sizementioning
confidence: 99%